Implementing AIDS Education - Huerta, Grace C. (Education Policy Analysis Archives, 1996)
The world has been challenged by the AIDS epidemic for 15 years. In 1985, the U.S. Department of Health and Human Services, Centers for Disease Control, allocated funds to all state departments of education to assist schools in the development of AIDS education policies and programs. Yet, these policies do not ensure that all students receive effective AIDS education. On September 21, 1991, the Arizona Legislature passed Senate Bill 1396, which requires public schools to annually provide AIDS education in grades K-12. The bill was rescinded in 1995. With prohibitive curriculum guidelines, limited teacher training opportunities and tremendous instructional demands, this educational policy was implemented in disparate forms. By examining the perspectives of the Arizona educators (representing three school districts), this qualitative study reveals how teachers ultimately controlled the delivery and nature of AIDS instruction based upon personal values, views of teacher roles, and their interpretation of the mandate itself.